Main EU requirements for goods safety and quality - Yemchenko, Iryna; Lehusha, Liliia (Видавництво Львівської політехніки, 2017)
The analysis of educational and scientific materials on the subject of adaptation of the national technical regulation system to the requirements of the EU. The research of key features of the European standardization system has been conducted. The main differences between the quality control system in the EU and in Ukraine are presented. The ways of adaptation of the domestic technical regulation system to the European space are proposed. In the conditions of the need to reorient the EU markets for domestic enterprises, there is a problem of finding opportunities to adapt the national system of standardization to European requirements. It updates the expediency of analyzing the basic requirements of the EU for the safety and quality of products, as well as finding solutions for the integration of domestic production capacities into the system of economic relations of the European Union.
Keywords: standardization; goods; import; quality; competitiveness; adaptation; requirements; reorientation; safety